Kendala Kegiatan Ekstrakurikuler Olahraga di SMA Negeri 1 Randublatung Kecamatan Randublatung Kabupaten Blora - Sanca Elfa Indrianjani; Harry Pramono (Universitas Negeri Semarang, 2023)
This study aims to explain sports extracurricular activities and the obstacles that affect sports extracurricular activities at SMA Negeri 1 Randublatung, Randublatung District, Blora Regency. This type of research is descriptive quantitative using survey methods and data collection techniques using questionnaires/questionnaires. The data analysis technique used quantitative descriptive as outlined in the form of a percentage. The results showed that the constraints on sports extracurricular activities at SMA Negeri 1 Randublatung came from the physiological factors of the respondents 55 or equal to 50% in the unfavorable category, the psychological factors of the respondents 62 or equal to 56.36% in the good category, the respondent's school factors 64 or the same with 58.18% in the good category, and the respondent's family factor 60 or equal to 54.55% in the good category. Conclusions: 1. The process of sports extracurricular activities at SMA Negeri 1 Randublatung is in good condition, 2. the constraints of various factors that cause the extracurricular activities do not run smoothly, in the form of a lack of interest in participating in sports extracurricular activities and have the potential to develop students who are talented, extracurricular activities were stopped due to Covid-19 so they will be carried out again after things return to normal